Sex differences in risk for Alzheimer's disease with extended maternal and paternal family history and vascular risk factors. The Cache County Study. (20th December 2022) - Vernon, Elizabeth K.; Gonzalez, Hector Leonardo; Schwartz, Sarah; Rattinger, Gail B.; Drewel, Mikaela; Smith, Ken Robert; DeBerard, Scott; Kauwe, John; Buhusi, Mona; Tschanz, JoAnn T
Abstract: Background: Age, family history (FH), APOE status, and vascular factors are known risk factors for Alzheimer's disease (AD). Sex differences in AD risk have been reported for some but not all of these factors. We examined sex differences in the association between FH and AD risk, studying the role of maternal/paternal lineage, parental longevity, and vascular factors in a population‐based cohort. Methods: 3677 participants (59% female) of the Cache County Memory Study [mean(SD) age = 75.75(7.11) years] were studied. FH of AD and health information were obtained from self‐report or Medicare claims and death certificates via data linkage through the Utah Population Database. AD cases were determined via clinical examination and Medicare claims and non‐cases via clinical examination or negative cognitive screenings. Results: Multivariate logistic regression models (covarying age, education, and APOE) found that individuals with a first‐ degree relative with AD was associated with a 58% and 66% increased risk of AD in males and females, respectively. In males, APOE Ɛ4 carriers with a history of exceptional maternal longevity (survival age 87+) had 3‐times the risk of AD than males with neither risk factor ( OR = 3.15, p interaction p = .020). Males with both exceptional maternal and paternal longevity (survival age 87+) had an 11% reduced risk of AD (OR = 0.894, interaction p = .041). A history of both maternal and paternal lineages of AD was associated with a 46% lower risk ( OR = 0.544) at trend level significance (interaction p = .054). In females, maternal lineage of AD was associated with a 56% increased risk of AD ( OR = 1.56; p = .005). Females with a history of congestive heart failure and paternal lineage of AD had twice the AD‐risk ( OR = 2.26, interaction p = .013) compared to females with neither risk factor. Parental exceptional longevity was not associated with AD risk in females. Conclusion: Risk for AD associated with family history varies by sex, maternal and paternal lineage of AD and exceptional parental longevity. Elucidating mechanisms and modifiable lifestyle factors underlying sex differences may facilitate developing primary AD prevention strategies.